A rare case of metachronous multiple supernumerary teeth in the bilateral premolar region of the mandible. Issue 2 (March 2017) - Koga, Kan-ichi; Yoshida, Ryoji; Nakamura, Takuya; Matsuoka, Yuichiro; Takeshita, Hisashi; Takahashi, Nozomu; Nakamoto, Masafumi; Hiraki, Akimitsu; Shinohara, Masanori; Nakayama, Hideki
Abstract: While supernumerary teeth are a common clinical phenomenon, metachronous supernumerary teeth in the same region are rare. A 12-year-old boy with multiple impacted supernumerary teeth in the mandible was referred to our hospital. A panoramic radiograph showed three impacted supernumerary teeth in the left incisor and bilateral premolar region of the mandible. All of the supernumerary teeth were extracted, and the dental follicles around the supernumerary teeth were removed. However, approximately two and half years later, two bilateral supernumerary teeth in the premolar region of the mandible were found in a routine panoramic radiograph. All of the supernumerary teeth were extracted again. The extracted teeth were similar in size and shape to the normal permanent premolars. A review of the previous literature suggests that this is a report of an extremely rare case of three impacted supernumerary teeth followed by metachronous bilateral supernumerary premolars. In addition, the supernumerary teeth that appeared after the first teeth extraction may have developed from the third dental laminae.